Cellulosic biomass-based sustainable hydrogels for wastewater remediation: Chemistry and prospective - Thakur, Sourbh; Verma, Ankit; Kumar, Vinod; Yang, Xiao Jin; Krishnamurthy, Satheesh; Coulon, Frederic; Thakur, Vijay Kumar (Elsevier, 2021)
Despite several technological improvements and achievements, wastewater treatment remains a serious issue internationally. Toxins in wastewater pose a significant threat to human health if left untreated. Due to macro-porous structure and different surface functionalization, cellulose biomass-based hydrogel is the most traditional adsorbent for removing harmful ions from wastewater. Recently, the introduction of several new cellulose derived materials have demonstrated their competitiveness in the removal of harmful ions. Numerous exceptional qualities better define this promising material, including high mechanical strength, large surface area and chemical inertness. This paper discusses the development status, preparation and modification methods of cellulose composites created by various materials (graphene, fly ash, graphene oxide and bentonite) which evaluates the research development and existing challenges in water treatment.
Keywords: Cellulose; Carboxymethyl cellulose; Cellulose-based hydrogels; Pollutants; Wastewater